Public Speaking - Ricky Telg (EDIS, 2011)
Knowing what to say and how to say it are foundational skills for all leaders; therefore, people promoting the agricultural industry need to know how to speak in face-to-face situations. This 3-page fact sheet shares the basics about gathering information and organizing, writing, and delivering speeches. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, August 2011.